Characteristics and Factors Associated with Hearing loss (Deafness) in Children Attending the Medical City Hospital, Baghdad, Iraq (Iraqi Journal of Medical Sciences, 2022)
Background: Hearing loss (HL) is one of the commonest and neglected childhood disabilities. According to the World Health Organization (WHO), most of childhood hearing impairment is preventable. Studies showed that 31% of hearing impairment cases are caused by prenatal and postnatal infections, 17% are birth-related causes, 4% are ototoxic medications and about 8% related to other causes such as maternal substance abuse.Objective: To review factors associated with HL in a sample of children attending the Medical City Hospital in the Pediatrics Outpatient Clinic and Auditory Clinic; including congenital, early, or late onset and to investigate risk factors associated with HL.Methods: A cross sectional study, included children
Keywords: Hearing loss; cochlear implant; otitis media